Reducing Dietary Sodium and Improving Human Health - Jacqui Webster (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This Special Issue of Nutrients, entitled "Reducing Dietary Sodium and Improving Human Health", welcomes the submission of manuscripts either describing original research or reviewing scientific literature related to salt reduction. Manuscripts should focus on population interventions for reducing dietary sodium and we are particularly interested in innovative approaches to changing the food environment and/or consumer behaviour. Manuscripts that discuss theoretical models informing the design of interventions for reducing dietary sodium are also welcome, as are studies from low or lower middle income countries. Potential topics may include, but are not limited to: Development/evaluation of regional or national strategies to reduce population salt intake Methodological issues related to measuring salt consumption patterns Use of policy or legislative approaches to reduce salt consumption Design and/or assessment of impact of behavioural change programs Modelling of the impact of interventions on salt intake and health outcomes.